PENGARUH DIMENSI KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDAPATAN DAERAH PROVINSI KALIMANTAN SELATAN - Adistya Dewi Ariffin; Laila Refiana Said (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
This research is aimed at finding out: (1) the influence of the job satisfaction on the work performance, (2) the influence of salary satisfaction on the work performance, (3) the influence of promotion opportunities on work performance, (4) the influence of supervision on work performance, (5) the influence of co-workers/colleagues on work performance , and (6) the influence of the job satisfaction, salary, promotion opportunities, supervision, co- workers/colleagues on work performance of the officer/civil servants at Dinas Pendapatan Daerah (Local Revenue Office) of South Kalimantan Province either partially or simultaneously. The analysis unit of this research is the entire staff of civil servants at Dinas Pendapatan Daerah (Local Revenue Office) of South Kalimantan Province, excluding the civil servants as well as part-time workers of the Unit Pelayanan Pendapatan Daerah (Service Unit of Local Revenue). The samples of this research are taken through census or saturated sampling method in which all population of the research which consisting of 88 employees are taken as the sample of this research. The data of this research are collected by using questionnaires, namely by providing a list of direct questions to the respondents. The variables of the research are measured through Likert scale. The data are then analyzed by using SPPS multiple linear regression analysis technique. The result of individual parameter sifnificance test (t-test) shows that (i) there is positive or significant influence of job satisfaction on work performance, (ii) there is positive or significant influence of salary satisfaction on works performance, (iii) there is positive or significant influence of promotion-opportunity satisfaction on works performance, (iv) there is positive or significant influence of supervision satisfaction on works performance, (v) there is positive or significant influence of co-workers/colleagues satisfaction on works performance. Additionally, the result of simultaneous test (F-test) shows that the score of F- value is greater than the score of F-table, with the confidence level at 95%. This means that there is simultaneous positive or significant influence of job satisfaction, salary satisfaction, promotion-opportunities satisfaction, supervision satisfaction dimension, and co- workers/colleagues satisfaction on work performance of the civil servants at Dinas Pendapatan Daerah (Local Revenue Office) of South Kalimantan Province.